2014
DOI: 10.2337/db14-0685
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Insulin Suppresses Endogenous Glucose Production in Humans Compared With Placebo in the Presence of Similar Venous Insulin Concentrations

Abstract: Intranasal insulin (INI) has been shown to modulate food intake and food-related activity in the central nervous system in humans. Because INI increases insulin concentration in the cerebrospinal fluid, these effects have been postulated to be mediated via insulin action in the brain, although peripheral effects of insulin cannot be excluded. INI has been shown to lower plasma glucose in some studies, but whether it regulates endogenous glucose production (EGP) is not known. To assess the role of INI in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
117
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 34 publications
9
117
6
1
Order By: Relevance
“…However, all the HGP-diminishing effects of intranasal insulin and oral diazoxide administration were in fact observed in healthy individuals [48,53,54], and they may not necessarily be reproducible in type 2 diabetes mellitus accompanied by obesity. The disturbance of central insulin action-mediated suppression of HGP has been reported in a rodent study using a high fat dietinduced obesity model [55], and dysfunction of central insulin action following high fat diet-induced obesity is reported to be due to inflammation of the hypothalamus and PI3K signal transduction failure caused by S6 kinase activation [55][56][57].…”
Section: Disclosurementioning
confidence: 98%
See 1 more Smart Citation
“…However, all the HGP-diminishing effects of intranasal insulin and oral diazoxide administration were in fact observed in healthy individuals [48,53,54], and they may not necessarily be reproducible in type 2 diabetes mellitus accompanied by obesity. The disturbance of central insulin action-mediated suppression of HGP has been reported in a rodent study using a high fat dietinduced obesity model [55], and dysfunction of central insulin action following high fat diet-induced obesity is reported to be due to inflammation of the hypothalamus and PI3K signal transduction failure caused by S6 kinase activation [55][56][57].…”
Section: Disclosurementioning
confidence: 98%
“…Indeed, it is possible to increase the cerebrospinal fluid insulin values without altering the peripheral blood insulin values by administrating 40 IU intranasal insulin to healthy individuals [52]. Intranasal administration of 40 IU insulin diminishes HGP under the condition of pancreatic clamp, which maintain a steady level of plasma insulin and glucagon by somatostatin administration [53]. Further, it has been reported that intrain hepatic glucose metabolism.…”
Section: Central Insulin Action-mediated Hgp Control and Type 2 Diabementioning
confidence: 99%
“…The FDA gave a Black Box Warning to the pulmonary administered insulin Exubera® since clinical studies reported a four-fold increase in the incidence of lung cancer among patients with a history of smoking. In 2007 Exubera® was discontinued and shifted back the interest to nasal insulin administration with very recent studies on beneficial metabolic effects of central insulin action [59,66,78]. Several companies continue their nasal insulin development programmes for the regimen of diabetes, all of them using different absorption enhancers like dodecyl-β-D-maltoside (Aegis therapeutics Inc.; [79]), micro crystalline cellulose (SNBL; [80]) and CriticalSorb™ (Critical Pharmaceuticals; [81]).…”
Section: Intranasal Insulin For Metabolic Diseasesmentioning
confidence: 99%
“…23,24 Moreover, intranasal insulin administration to healthy humans decreases endogenous glucose production. 25 Increased endogenous glucose production is the main source of hyperglycemia in individuals with diabetes 26 and thus a hallmark of underlying pathophysiology of this serious medical illness.…”
mentioning
confidence: 99%